MCF10CA Breast Cancer Cells Utilize Hyaluronan-Coated EV-Rich Trails for Coordinated Migration - Aaltonen, Niina; Kyykallio, Heikki; Tollis, Sylvain; Capra, Janne; Hartikainen, Jaana M.; Matilainen, Johanna; Oikari, Sanna; Rilla, Kirsi (Frontiers in Oncology, 2022)
Invasion of tumor cells through the stroma is coordinated in response to migratory cues provided by the extracellular environment. One of the most abundant molecules in the tumor microenvironment is hyaluronan, a glycosaminoglycan known to promote many hallmarks of tumor progression, including the migratory potential of tumor cells. Strikingly, hyaluronan is also often found to coat extracellular vesicles (EVs) that originate from plasma membrane tentacles of tumor cells crucial for migration, such as filopodia, and are abundant in tumor niches. Thus, it is possible that hyaluronan and hyaluronan-coated EVs have a cooperative role in promoting migration. In this work, we compared the hyaluronan synthesis, EV secretion and migratory behavior of normal and aggressive breast cell lines from MCF10 series. Single live cell confocal imaging, electron microscopy and correlative light and electron microscopy experiments revealed that migrating tumor cells form EV-rich and hyaluronan -coated trails. These trails promote the pathfinding behavior of follower cells, which is dependent on hyaluronan. Specifically, we demonstrated that plasma membrane protrusions and EVs left behind by tumor cells during migration are strongly positive for CD9. Single cell tracking demonstrated a leader-follower behavior, which was significantly decreased upon removal of pericellular hyaluronan, indicating that hyaluronan promotes the pathfinding behavior of follower cells. Chick chorioallantoic membrane assays in ovo suggest that tumor cells behave similarly in 3D conditions. This study strengthens the important role of extracellular matrix production and architecture in coordinated tumor cell movements and validates the role of EVs as important components and regulators of the tumor matrix. The results suggest that tumor cells can modify the extracellular niche by forming trails, which they subsequently follow coordinatively. Future studies will clarify in more detail the orchestrated role of hyaluronan, EVs and other extracellular cues in coordinated migration and pathfinding behavior of follower cells.